1985
DOI: 10.1136/bmj.290.6465.347
|View full text |Cite
|
Sign up to set email alerts
|

Use of anti-inflammatory drugs by patients admitted with small or large bowel perforations and haemorrhage.

Abstract: The intake of anti-inflammatory drugs by 268 patients with colonic or small bowel perforation or haemorrhage was compared with that by a group of patients, matched for age and sex, with uncomplicated lower bowel disease. Patients with perforation or haemorrhage were more than twice as likely to be takers of anti-inflammatory drugs, but no association was detected with the intake of other types of drugs, particularly cardiovascular drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
9

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(103 citation statements)
references
References 5 publications
2
91
1
9
Order By: Relevance
“…In another retrospective study, it is noted that those patients who were taking NSAIDs were twice as likely to have small and large bowel perforations or hemorrhage in comparison with control patients [10], further supporting our presumption in this case. …”
Section: Discussionsupporting
confidence: 75%
“…In another retrospective study, it is noted that those patients who were taking NSAIDs were twice as likely to have small and large bowel perforations or hemorrhage in comparison with control patients [10], further supporting our presumption in this case. …”
Section: Discussionsupporting
confidence: 75%
“…A connection between corticosteroid treatment and severe septic complications of diverticular disease has been reported.3 In addition, an increased risk of perforation of the small and large bowel, not necessarily related to diverticular disease, has been found in patients who were taking a variety of anti-inammatory drugs. 4 We present here evidence that supports an association between severe septic complications of diverticular disease and both corticosteroid and non-steroidal anti-inflammatory drug treatment.…”
Section: Commentmentioning
confidence: 73%
“…It is well known that NSAIDs induce gastroduodenal ulcers in humans (13,21,23,24,32). Moreover, it was reported recently that NSAIDs induce ulceration in the small intestine and some patients who received NSAIDs chronically died of perforation of the small intestine (1,6,22,28,30). Bjarnason et al (3,4) reported that 70% of the patients receiving long-term NSAID therapy have an asymptomatic enteropathy and occasionally may suffer from intestinal ulcers and strictures.…”
Section: Discussionmentioning
confidence: 99%